A Randomized Controlled Trial: Regenerative Effects, Efficacy and Safety of Erythropoietin in Burn and Scalding Injuries - Günter, Christina I.; Machens, Hans-Günther; Ilg, Felicitas P.; Hapfelmeier, Alexander; Jelkmann, Wolfgang; Egert-Schwender, Silvia; Giri, Shibashish; , “EPO in Burns” Study Group; Bader, Augustinus (Frontiers in Pharmacology, 2018)
In adult’s burn injuries belong to the top 15 causes of injury. Annually more than a million patients receive specialized treatment. Improving burned patients’ outcomes is still a challenge. Effects of erythropoietin (EPO) are reported to be pro-angiogenic, pro-regenerative, anti-inflammatory, immunomodulatory and hypoxia/ischemia protective. Study objectives were to demonstrate cytoprotective and regenerative effects of EPO in burned patients in terms of improved wound healing, reduced morbidity and mortality. This was a prospective, placebo-controlled, randomized, double-blind trial. The trial was conducted in 13 specialized burn care centers in Germany. Adult Patients with 2b° or 3° burn injuries were included. Patients received state of the art burn care including obligatory split skin graft transplantation. Study medication was EPO or placebo every other day for 21 days. Between 12/08 and 06/14, 116 patients were randomized, 84 received study medication (EPO 45, Placebo 39). Primary endpoint analysis revealed inconclusive results, as only a minority of patients reached the primary endpoint (100% re-epithelialization: EPO: 23% (9/40); Placebo 30% (11/37)). Several secondary endpoints such as SOFA score (morbidity), EPO level in blood and wound healing onset revealed clinical, and statistically significant results in favor of the EPO group. Adverse Events (AEs) and Severe Adverse Events (SAEs) were in expected ranges; AEs EPO: 80%, (36/45), Placebo: 77%, (30/39); SAEs EPO: 24%, (11/45), Placebo: 24%, (8/39). Out of 84 patients two died, one per group, thus mortality was lower than expected. Results (SOFA score) indicate a lower morbidity of the EPO group, suggesting pro-regenerative effects of EPO in burned patients. Higher EPO levels might influence the faster onset of re-epithelialization in the first 10 days of the treatment. Both effects could reveal new therapeutic options.